Importancia de la distancia y el ambiente en la estructura genética de anuros neotropicales - Galarza Ferrín, Gabriela (PUCE, 2016)
The study of landscape features that influence genetic structure of wild populations can help us understand the first steps of biological divergence. Populations diverge when there is restriction to gene flow, which can happen due to environmental and geographic factors. However, the relative importance of these processes in generating genetic diferentiation at the neotropical landscape is poorly understood. This study aims to quantify the effect of isolation by environment (IBE) and isolation by distance (IBD) in the spatial genetic structure of nine neotropical frog species by using Structural Equation Modelling. Our analysis shows that IBD is the most important factor in all the species (0.61 IBD vs. 0.33 IBE on average) although IBE also has a significant effect. This suggests that spatial genetic structure is mainly correlated to geographic rather than ecological factors in the neotropical landscape.